Fate and sublethal effects of metals during amphibian metamorphosis: A systematic review. Issue 23 (2nd December 2022) - Hill, Danielle; Cresswell, Tom; Bennett, William; Lanctôt, Chantal
Abstract: Amphibians provide essential ecosystem services and are facing global decline. Exposure to contaminants is a contributing factor to this decline, with permeable skin and early aquatic life likely increasing amphibian susceptibility. Their vulnerability may also be increased through metamorphosis, which involves degeneration of tissues and high energy expenditure. Exposure to metal contaminants may also result in delays to metamorphosis or reduced growth. Understanding how metal burdens change during metamorphosis and the effects metals have on postmetamorphic amphibians is essential to ensure water quality guidelines offer sufficient protection. A systematic review of the literature was conducted to identify the changes in whole-body metal burden and biodistribution pre and postmetamorphosis and the effects of metal exposures on the timing of metamorphosis and size of animals postmetamorphosis. Premetamorphic amphibians were found to have higher metal concentrations than postmetamorphic, suggesting these metals can be largely excreted prior to or during metamorphosis. Only two articles were identified that compared changes in metal biodistribution during metamorphosis, with both reporting decreasing concentrations in the gut from pre to postmetamorphosis. No laboratory studies identified significant effects relating to metamorphosis at concentrations below USEPA chronic water quality criteria. However, delays to timing or growth were observed in field studies where all analyzed metals were below criteria. Many articles did not meet the suggested minimum reporting standards, particularly for the reporting of metal exposure concentrations and physico-chemical conditions of exposure solutions. Graphical abstract: UF0001